1998
DOI: 10.1182/blood.v92.7.2322.2322_2322_2333
|View full text |Cite
|
Sign up to set email alerts
|

The Importance of Diagnostic Cytogenetics on Outcome in AML: Analysis of 1,612 Patients Entered Into the MRC AML 10 Trial

Abstract: Cytogenetics is considered one of the most valuable prognostic determinants in acute myeloid leukemia (AML). However, many studies on which this assertion is based were limited by relatively small sample sizes or varying treatment approach, leading to conflicting data regarding the prognostic implications of specific cytogenetic abnormalities. The Medical Research Council (MRC) AML 10 trial, which included children and adults up to 55 years of age, not only affords the opportunity to determine the independent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
33
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(45 citation statements)
references
References 33 publications
2
33
1
Order By: Relevance
“…All cases showed five or more copies of RUNX1 probe signals. Patient 1 displayed a highly complex karyotype of 45,XX,der(3)inv(3)(p25q25)add(3) (q11.2),-5,-7,+12,-14,add(14)(p11.2),+19,hsr(21) (q22) [3]/45,sl,-4,-12,+ r,+ mar [15]/46,sdl1,+ 8 [2] in three clones, each having monosomy 5 and 7 and an hsr on chromosome 21 (Fig. 1a).…”
Section: Karyotype and Fish Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…All cases showed five or more copies of RUNX1 probe signals. Patient 1 displayed a highly complex karyotype of 45,XX,der(3)inv(3)(p25q25)add(3) (q11.2),-5,-7,+12,-14,add(14)(p11.2),+19,hsr(21) (q22) [3]/45,sl,-4,-12,+ r,+ mar [15]/46,sdl1,+ 8 [2] in three clones, each having monosomy 5 and 7 and an hsr on chromosome 21 (Fig. 1a).…”
Section: Karyotype and Fish Resultsmentioning
confidence: 99%
“…Acute myeloid leukemia (AML) is a genetically heterogeneous disease including several distinct subtypes based on cytogenetic and molecular characteristics [1,2]. Chromosomal and molecular genetic characteristics are a major feature for risk stratification to predict outcomes and guide treatment selection [3]. Although 5-year survival of adult AML has improved in the past decades due to advances in treatment, including targeted therapies and risk-adapted regimens, more than two-thirds of AML patients do not survive beyond 5 years and most relapse [4].…”
Section: Introductionmentioning
confidence: 99%
“…Efforts to advance our understanding of molecular alterations in pediatric AML 3,4,15,17,22,44,51 have revealed profound heterogeneity and improved understanding for how mutations and structural alterations impact treatment outcome. In the current study, we revealed that these molecular alterations share a close relationship with LSC gene expression, wherein LSC genes can accurately discriminate between AML molecular subtypes on the basis of unsupervised clustering alone.…”
Section: Discussionmentioning
confidence: 99%
“…Acute myeloid leukemia (AML) remains a therapeutic challenge with high mortality rates despite intensive and myeloablative therapies 1,2 . Structural and sequence alterations have been linked to outcomes in AML and have been used for risk-based therapy allocation with modest success [3][4][5][6][7][8][9][10] . However, given the vast heterogeneity of AML, conventional cytogenetic and molecular (cytomolecular) biomarkers have not yielded a robust prognostic model to date.…”
mentioning
confidence: 99%
“…Based on genetic abnormalities, the European Leukemia Network (ELN) risk stratification system classifies AML patients into three risk groups: favorable, intermediate, and adverse (Table S1) (6). The cytogenetic abnormalities associated with AML are recognized as being the most valuable prognostic factors (7). However, cytogenetically normal AML (CN-AML) represents the largest AML subset, comprising 45%-60% of all cases (8,9).…”
Section: Introductionmentioning
confidence: 99%